Aplikasi Geofoam Sebagai Material Timbunan di Atas Tanah Lunak - Irpan Hidayat; Andryan Suhendra (Bina Nusantara University, 2011)
Geofoam is a geosintetik material made of Expanded Polystyrene (EPS) and Xtruded Polystyrene (XPS), which has a low weight property which makes geofoam widely used as a lightweight fill material and has been applied in Europe, especially in Eastern Europe. This is a preliminary research that emphasizes on the use of geofoam as a fill material on soft ground through theoretical analysis using Plaxis program. Supporting data used covers data of basic and fill ground taken from specific locations which are planned for subsequent research as a field test. Based on the Plaxis program results, the use of geofoam as a fill material give a higher safety factor value with a smaller deformation compared to laterite soil. This result indicates that the use of geofoam as a fill material can be considered to be applied in the country.